The Effect of Compensation and Loyalty on Work Discipline of Employee in One of Indonesian Commercial Bank - Nawiyah Nawiyah; Dyah Handayani Dewi; Muh. Risal Tawil; Mohammad Rizky Yahya; Abd. Jalil M. (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
Every business or organization needs human resources (HR) to function effectively. Companies must be able to maximize both their use of and management of their human resources. Employee performance expectations, which must be met in order for the organization to succeed, are inextricably linked to human resource management. Employees are a company's most valuable asset and play an important part in it as thinkers, planners, and controllers of business operations, thus it is important to take care of them. Employees with a high level of discipline are good employees. This study attempts to ascertain the simultaneous or partial effects of pay and loyalty on the work discipline of one of commercial banks in Indonesia. All employees served as the sample in this study, which used a purposive sampling technique. This study's technique of analysis involves multiple linear regression. The findings of the F test indicate that the pay and loyalty variables concurrently have a positive and substantial impact on employee work discipline, as indicated by the F value of 0.000 < 0.05. The pay and loyalty variables both have a positive and substantial impact, as shown by the t test. R Square corrected to 0.559.